El matrimonio civil igualitario como forma de ejercer el derecho a la igualdad y no discriminación (Tema Central) - Orellana Ramírez, María Inés (2019)
A homosexual couple based on Advisory Opinion OC-24/17, want to celebrate between them civil marriage. Petition denied due to several reasons, as such, they present a protection action. In first instance the demand is accepted, while the superior judge not accept the petition. This is where we must consider whether or not the right to equality and non-discrimination is violated and not only of the petitioners but in general to people with a different sexual orientation, a category protected by the current Ecuadorian Constitution. In addition to determining if the aforementioned international instrument is part of the constitutionality block since, if it were affirmative, it would be part of the current legislation and, therefore, of mandatory compliance.